2019
DOI: 10.1038/s41467-019-10310-0
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate causal mixture model quantifies polygenic overlap between complex traits beyond genetic correlation

Abstract: Accumulating evidence from genome wide association studies (GWAS) suggests an abundance of shared genetic influences among complex human traits and disorders, such as mental disorders. Here we introduce a statistical tool, MiXeR, which quantifies polygenic overlap irrespective of genetic correlation, using GWAS summary statistics. MiXeR results are presented as a Venn diagram of unique and shared polygenic components across traits. At 90% of SNP-heritability explained for each phenotype, MiXeR estimates that 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
249
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 263 publications
(294 citation statements)
references
References 58 publications
5
249
0
1
Order By: Relevance
“…Recent large-scale genome-wide association studies (GWAS) have identified a large number of single-nucleotide polymorphisms (SNP) associated with psychiatric disorders such as schizophrenia (SCZ) 1 , bipolar disorder (BD) 2 , major depression (MD) 3 , attention deficit hyperactivity disorder (ADHD) 4 , autism spectrum disorders (ASD) 5 , post-traumatic stress disorder (PTSD) 6 , and anxiety (ANX) 7 . In addition to substantial polygenicity, previous findings have documented genetic overlap between disorders [8][9][10][11] , even in the absence of genetic correlations as recently demonstrated for schizophrenia and educational attainment 12,13 . Adding to the complexity, psychiatric disorders also overlap with multiple complex traits, such as BMI 14 and cardio-metabolic diseases 15 .…”
Section: Introductionmentioning
confidence: 85%
“…Recent large-scale genome-wide association studies (GWAS) have identified a large number of single-nucleotide polymorphisms (SNP) associated with psychiatric disorders such as schizophrenia (SCZ) 1 , bipolar disorder (BD) 2 , major depression (MD) 3 , attention deficit hyperactivity disorder (ADHD) 4 , autism spectrum disorders (ASD) 5 , post-traumatic stress disorder (PTSD) 6 , and anxiety (ANX) 7 . In addition to substantial polygenicity, previous findings have documented genetic overlap between disorders [8][9][10][11] , even in the absence of genetic correlations as recently demonstrated for schizophrenia and educational attainment 12,13 . Adding to the complexity, psychiatric disorders also overlap with multiple complex traits, such as BMI 14 and cardio-metabolic diseases 15 .…”
Section: Introductionmentioning
confidence: 85%
“…Several available Bayesian approaches (Giambartolomei et al 2014;Pickrell et al 2016) explore whether two association signals in the same genomic region obtained from two different GWAS share a single causal variant or multiple causal variants. Frei and colleagues performed a similar analysis at the genome-wide level, estimating the proportion of phenotype-specific causal variants and shared variants between complex phenotypes using GWAS summary data, while controlling for shared participants (Frei et al 2019). The analysis demonstrates how the shared polygenic component may constitute a large fraction of the genetic architecture of one phenotype, while constituting a smaller fraction of the architecture of a phenotype with larger polygenicity.…”
Section: Comparison To Other Cross-trait Analytical Toolsmentioning
confidence: 99%
“…Other studies have also shown a strong positive correlation between SZ genetic risk and EA, as previously mentioned [27,47,54,60,62,[67][68][69][70] albeit few studies found non-significant or discrepant results [53,55]. Using the cFDR statistical approach, 10 gene loci were associated with SZ and EA/high EA, with effects in opposite directions [69].…”
Section: Implication Of Cognition/ea On the Risk For Schizophrenia Anmentioning
confidence: 71%